Health risk assessment to xenoestrogen through atmospheric PM2.5 particles: A case study in Suzhou - Minhao Wang; Dongling Li; Ting Tong; Yuwei Xia; Haifei Zhang; Xiao Zhou; Wen Jiang; Kui Chen; Fang Wang; Peng Zhao; Lei Han (Ecotoxicology and Environmental Safety)
Xenoestrogens, classified as endocrine disruptors, can be inhaled through atmospheric particles, leading to adverse health effects such as cancer and developmental abnormalities. This research focused on analysing the monthly distribution, seasonal variation, and health impacts of six target xenoestrogens (dibutyl phthalate (DBP), di(2-ethylhexyl) phthalate (DEHP) and diisobutyl phthalate (DIBP)), bisphenol A (BPA), and alkylphenols (nonylphenol (NP) and 4-tert-octylphenol (4-t-OP)) in atmospheric PM2.5 at campus of Xi'an Jiaotong-Liverpool University from September 2021 to September 2023. The monthly average concentration of xenoestrogens was measured at 20 ng·m−3, while the mass concentration of PM2.5 varied between 1.75 and 217.36 μg·m−3. BPA was the predominant xenoestrogen in campus, with a peak of 126.52 ± 0.67 ng·m−3. The average concentrations of BPA, DBP and DEHP at campus were significantly higher in winter compared to summer in 2022. The non-carcinogenic risk (hazard index (HI) < 1) and carcinogenic risk (Incremental Lifetime Cancer Risk (ILCR)< 10−6) on non-dietary basis for all residents did not exceed the threshold limit at campus. However, the HI (2.82 ×10−5 - 3.53 ×10−3) and ILCR (1.48 ×10−12) values for infants and young children are significantly higher than other age groups, indicating a heightened risk of exposure to xenoestrogens. Given the rising global concern over air quality and its impact on public health, our work contributes valuable data that can inform policy and regulatory measures aimed at mitigating the health risks of exposure to xenoestrogen in the atmosphere.